2012
DOI: 10.1111/j.1365-2524.2012.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Social capital - a neglected issue in diabetes control: a cross-sectional survey in Iran

Abstract: What is known about this topic dSocial capital has a protective effect on risk-taking behaviours or corresponding disease outcomes. There is a strong association between social capital and management of chronic disease. What this paper adds dSocial capital has a promising effect in the control of diabetes in Iran.d Among social capital dimensions, 'trust and solidarity' and 'empowerment and political action', may determine how effectively that patient's diabetes is managed. AbstractGlycaemic control is an esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“… Age Female 1.48(1.07-2.05) Educational level/ Age ,≥ 55 3.31 (2.38-4.60) Economic status/ Illiterate 1.37 (0.99-1.90) Residence Urban 1.52 (1.10-2.10) Low and medium economic status 1.16 (0.46-2.91) 6 Shahraki, M. et al 2012[ 32 ] Cross sectional study, Clinical Based/ Zahedan 2012 Overweight and obese women/Non random sampling n=811 Female 20–60 Age/Educational level FBS levels and SEF Age and education significantly associated with FBS levels. Encourage to physical activity and healthy diet among women ≤ Age50 3.8 (1.798.45) Educational level≤12 1.9 (1.25 -3.15) c) Diabetes control NO Reference Study design and Setting Study year Participants and their recruitment Sex Age (Year) Socioeconomic Factors OR (95% CI) Main Conclusion Suggestion 7 Farajzadegan, Z. et al 2013[ 33 ] Cross sectional study, Population based/ ...…”
Section: Resultsmentioning
confidence: 99%
“… Age Female 1.48(1.07-2.05) Educational level/ Age ,≥ 55 3.31 (2.38-4.60) Economic status/ Illiterate 1.37 (0.99-1.90) Residence Urban 1.52 (1.10-2.10) Low and medium economic status 1.16 (0.46-2.91) 6 Shahraki, M. et al 2012[ 32 ] Cross sectional study, Clinical Based/ Zahedan 2012 Overweight and obese women/Non random sampling n=811 Female 20–60 Age/Educational level FBS levels and SEF Age and education significantly associated with FBS levels. Encourage to physical activity and healthy diet among women ≤ Age50 3.8 (1.798.45) Educational level≤12 1.9 (1.25 -3.15) c) Diabetes control NO Reference Study design and Setting Study year Participants and their recruitment Sex Age (Year) Socioeconomic Factors OR (95% CI) Main Conclusion Suggestion 7 Farajzadegan, Z. et al 2013[ 33 ] Cross sectional study, Population based/ ...…”
Section: Resultsmentioning
confidence: 99%
“…In this review, most studies are from Occident in 17 included articles, while in LMIC these kinds of studies are rare (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), so the effect of social capital on NCDs in these countries is not known. Social capital was measured by individual cognition and behavior, and the ecological data were aggregated from the individual level, and there is no effective method to measure social capital precisely and directly at present.…”
Section: Discussionmentioning
confidence: 99%
“…The social capital is examined in six domains including groups and networks, trust and agreement, cooperation and collective action, information and communication, social cohesion and inclusion as well as empowerment and political performance (9). Several studies have shown that social capital can play a role in reducing the incidence rate of headaches (10). The purpose of this study was to examine the social capital level in people with primary headaches compared with the control group.…”
Section: Introductionmentioning
confidence: 99%